Effect of mesh coarseness on slope stability analysis using 2D and 3D finite element method - Noraida Mohd Saim; Anuar Kasa (Penerbit Universiti Kebangsaan Malaysia, 2024)
A comprehensive understanding of slope stability is essential for ensuring the safety and durability of structures built on or near slopes and mitigating the risks associated with landslides and slope failures. Slope stability is typically evaluated using the factor of safety (FOS) based on the critical slip surfaces. The calculation of FOS is commonly executed using Limit Equilibrium Method (LEM) by dividing the slope into several vertical slices. However, the stability analyses using Finite Element Method (FEM) have gained significant attention in geotechnical engineering due to their ability to simulate slope behaviour and predict stability accurately by employing mathematical models and computational algorithms. Hence, this paper aims to analyse the FOS of the unreinforced slope using 2D FEM and 3D FEM conducted through computer software while examining the influence of different mesh coarseness. Besides that, the formation of critical slip surfaces and the displacement behaviour of the slope are also presented. A slope geometry model was analysed using PLAXIS 2D and PLAXIS 3D with different mesh coarseness. The findings were compared and discussed. The findings reveal that the values of FOS generated by 3D FEM are slightly larger compared to 2D FEM analysis, ranging from 1.27% to 2.56%. On the other hand, the effect of mesh coarseness indicates that coarser mesh sizes yield higher FOS values compared to finer mesh sizes. The shape, location and depth of the critical slip surfaces are consistent for each analysis in both methods. However, the maximum displacement values differ for each mesh coarseness, as the locations of maximum total displacement are identified at different nodes due to varying numbers of elements but still within the same potential failure zone. Overall, this comparative study is crucial in ensuring the validity of the performed analyses. Understanding the capabilities and limitations of 2D and 3D numerical analyses to achieve reliable and accurate results is important to balance mesh coarseness and computational efficiency.